Daily Consumption of Stevia Drops Effects on Glycemia, Body Weight and Energy Intake: Results from a 12-Week, Open-Label, Randomized Controlled Trial in Healthy Adults. (29th May 2020) - Stamataki, Nikoleta; Crooks, Benjamin; McLaughlin, John
Abstract: Objectives: Stevia is a non-nutritive sweetener providing sweet taste with zero calories that could constitute an effective strategy toward sugar reduction. This study tested the effects of daily consumption of stevia drops on glycemia, body weight (BW) and energy intake in healthy normal weight adults, non-habitual consumers of non-nutritive sweeteners. Methods: Twenty eight healthy participants were randomly assigned to the stevia group ( n = 14, mean age: 25 ± 5.5 y, mean body mass index: 22 ± 1.8 kg/m2) and were required to consume 5 drops of a commercially available stevia extract twice daily along with their habitual drinks, or to the control group ( n = 14, 25 ± 4.2 y, 21 ± 1.5 kg/m2) and were instructed not to change anything in their diet for 12 weeks. Both groups were encouraged to maintain their usual diet and physical activity habits. At baseline and week 12, glucose response to an oral glucose tolerance test (OGTT) was measured; BW and energy intake were assessed at baseline, week 6 and week 12. Results: There was no significant difference in glucose response to the OGTT over the 12 weeks in any study group. However, there was a significant main effect of participant group on BW change over the 12 weeks (F(1, 26) = 5.56, P = 0.026), showing that stevia consumption prevented weight gain (ΔWeight at week 12 = −0.22 ± 0.32 kg for stevia, +0.89 ± 0.39 kg for the control group). Energy intake was significantly decreased between baseline and week 12 in the stevia group (ΔEnergy at week 12 = −344 ± 80.6 kcal, P = 0.003), however no change in energy intake was found in the control group (ΔEnergy = +13.6 ± 125 kcal, P = 0.973). Conclusions: These results suggest that daily consumption of stevia in real-life doses does not affect glycemia in healthy normal-weight individuals, but could aid toward weight maintenance and moderation of energy intake. More research is warranted to explore these promising findings further in individuals with overweight/obesity and/or individuals with impaired glucose tolerance (i.e., pre-diabetes/diabetes). Clinicaltrial.gov identifier: NCT03993418. Funding Sources: This project has received a N8 AgriFood Pump Priming Award. Ms Stamataki has a BBSRC DTP Case Studentship.